Improved low-frequency sound absorption of porous silicone rubber resonance sheet with periodic cavities. Issue 3 (September 2022) - Peng, Longgui; Zhao, Pu; Cheng, Huanquan; He, Qirui; Du, Lifei
Since the development of advanced sound absorption material is highly critical in noise control applications, anechoic coatings, and acoustic metamaterials, both fabrication technology and structure design are significant in the achievement of broadband and strong absorption performance in the low sound frequency range. In this work, the silicone rubber resonance absorption sheet with periodic cavities is prepared via inserting cylindrical steel strips with different diameters into the non-vulcanized colloid. Effects of size and arrangement of cavities on the sound absorption properties, as well as the corresponding mechanical properties, are investigated and discussed. Results indicate that periodic pattern designs could further improve the low-frequency sound absorption performance of silicone rubber foams, and increasing the cavity diameter could significantly improve the sound absorption efficiency of the prepared samples in the middle- and low-frequency range from 125 to 2000 Hz. Particularly, increasing the number of the layered cavities could also improve the sound absorption efficiency. The consumption of sound energy in the prepared silicone rubber resonance sheet is discussed, which could be attributed to the synergistic effect in different spatial scales.